Negara Ummat dan Pendidikan Islam Bernegara: Strategi Kebangkitan Menuju 2045 - Hamijaya, Nunu A (PT. Student Rihlah Indonesia, 2025)
The existence of the Ottoman Empire (1299–1924) as a political power and center of Islamic civilization represents a crucial phenomenon in world history. This study aims to analyze the political system, governance, state structure, and the development of intellectual, scientific, religious, and cultural life during the Ottoman era, covering the empire’s establishment, golden age, and eventual decline. The research adopts a qualitative historical method through literature review of secondary sources (books, journals, manuscripts) and translated primary sources (archives, works of scholars). The findings reveal: (1) A political system based on absolute monarchy and a hybrid legal framework (Hanafi sharia-kanun) supported imperial expansion and multiethnic stability; (2) A structured education system (madrasah) and state patronage fostered advancements in applied sciences (astronomy, medicine, architecture) and cultural expression in arts and language; (3) Islamic spirituality was mobilized through the caliphate title and ghaza narrative; (4) The millet system accommodated diversity, though bureaucratic stagnation and modernizing pressures led to decline. The novelty of this study lies in its holistic approach that integrates political, intellectual, and cultural aspects, revealing the interconnection between power and civilizational dynamics. The implications offer a comprehensive perspective for Islamic historical studies, emphasizing that Ottoman glory was sustained through the integration of knowledge, religion, and governance rooted in Islamic principles.